The Electronic Market Place as a Key Business Model in Trade - Galabova, Violeta (Research Papers, 2021)
Digitalisation has transformed trade over the last two decades. New business models have been developed through interdependence and synergy in the activities of many participants. Such a business model is the electronic marketplace, which connects consumers with suppliers in a united ecosystem. The purpose of this article is to derive the characteristics of the e-marketplace and the advantages of this business model that stimulate its development. To achieve this goal, a content analysis of academic publications was applied, statistical data were used, terminological clarifications were made. The study is limited to marketplace platforms trading in goods and services, excluding social media platforms, operating systems and payment systems.
Keywords: E-marketplace; Business model; Trade; Platform